PENGARUH KEUANGAN, KUALITAS AUDITOR, KEPEMILIKAN PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Difa, Rivenski Atwinda; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to analysis some factors that have influence to the going concern audit opinion.The thing that can become the consideration of the auditor in giving going concern audit opinion canbe done by seeing internal factor e.g. financial condition and audit quality that is related to the auditorperformance in giving going concern audit opinion from the previous year as a consideration forgiving going concern audit opinion for the following year, and company ownership can be aconsideration in giving going concern audit opinion since the company will be protected fromfinancial difficulty with the presence of company ownership. This research has been carried out bymeans of secondary data search and by using 12 samples from the list of manufacturing companies inIndonesia Stock Exchange during the periods of 2009, 2010, 2010, 2011, and 2012. The logisticregression analysis is employed as the technique in this research to test the hypothesis. The result ofhypothesis test shows that audit quality has positive influence on going concern audit opinion. Thefinancial condition variable and company ownership has negative influence on going concern auditopinion.Keywords: Going Concern Audit Opinion, Previous Year Opinion, Financial Condition, AuditQuality, Company Ownership